2021
DOI: 10.1590/s1984-29612021057
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic effect of four extracts obtained from Caesalpinia coriaria foliage against the eggs and larvae of Haemonchus contortus

Abstract: To investigate the in vitro anthelmintic efficacy of dividivi (Caesalpinia coriaria), a traditional medicinal plant used in Central America and the northern part of South America, extracts from the foliage of this plant were subjected to the egg hatching test (EHT) and larval exsheathment inhibition test (LEIT), against Haemonchus contortus. Four different extracts were evaluated: acetone-water (AW), methanol-water (MW), acetone-water-dichloromethane (AWD) and methanol-water-dichloromethane (MWD). The concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…A total condensed tannins content of 7.72 mg/gdw was reported by Pineda-Peña et al [40]. The values for condensed and total polyphenols released from cascalote pods in the present work are 120-521% and 265-288% higher than the values previously reported [38][39][40].…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…A total condensed tannins content of 7.72 mg/gdw was reported by Pineda-Peña et al [40]. The values for condensed and total polyphenols released from cascalote pods in the present work are 120-521% and 265-288% higher than the values previously reported [38][39][40].…”
Section: Discussioncontrasting
confidence: 53%
“…Using extraction by maceration with methanol, Sánchez et al [38] reported values of 21.71 mg/gdw for condensed tannins and 32.06 mg/gdw for total tannins. Rojas-Morales et al [39] reported values for condensed and total tannins of 13 and 34 mg/gdw, respectively. A total condensed tannins content of 7.72 mg/gdw was reported by Pineda-Peña et al [40].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation